Suicide resilience: A concept analysis - Wang, Xinlu; Lu, Zhongqiu; Dong, Chaoqun (Frontiers in Psychiatry, 2022)
Objective: Suicide resilience is gaining increasing attention from researchers because of its potential role in preventing suicide. However, it has not been clearly analyzed, and there are various meanings and terms regarding this issue. The purpose of this analysis, therefore, was to conceptualize the concept of suicide resilience. Methods: Walker and Avants's method of concept analysis was used to identify the antecedents, attributes, and consequences of suicide resilience. The literature was searched using PubMed, PsychINFO, Embase, Scopus, Web of Science, CINHAL, CNKI, and WangFang databases with no limitation on publication date. The search included peer-reviewed journal articles and dissertations related to suicide resilience published in English or Chinese. Results: 49 articles were identified to provide information for this concept analysis. Five defining attributes of suicide resilience were identified: social support, meaning in life, coping strategies, positive thinking, and a sense of responsibility. Antecedents of suicide resilience were high suicide risk events, and consequences of suicide resilience were keeping vulnerable individuals stay away from or overcoming suicidality. Conclusions: The result of the analysis provided a more clear definition of suicide resilience. The identified defining attributes, antecedents, and consequences can be further tested and used to develop potential interventions. Future research is needed and will help to advance our understanding of the scope.